Kearifan Lokal Sasi Terhadap Eksistensi Teripang di Desa Lelingluan, Kecamatan Tanimbar Utara, Kabupaten Kepulauan Tanimbar - Kormasela, Dince Avia; Nifanngelyau, Jakobus; Srue, Olivir (KAMBOTI: Jurnal Sosial dan Humaniora, 2023)
Sasi is one of the indigenous wisdoms that have been preserved in the Tanimbar Archipelago Regency, North Tanimbar District, and particularly in Lelingluan Village. The Lelingluan village community is rich in culture and local wisdom, namely Sasi local wisdom. The local wisdom, or sasi, is usually used to conserve, maintain, and protect natural resources, both on land and at sea, with the aim that all communities can enjoy the results together. Sasi, which is usually done in general and involves traditional leaders and their implementation through customary law procedures, is for sea cucumbers. This is because sea cucumbers are one of the marine resources that can meet the needs of the Lelingluan village community, so their existence must be maintained properly. Sea cucumbers, on the other hand, are one of Lelingluan village's properties; hence, sea cucumber sasi is included in the state sasi and must go through customary (oath) implementation before proceeding with ecclesiastical procedures. The existence of sea cucumbers in Lelingluan village can be preserved thanks to the local wisdom of sasi. This research aimed to describe the local wisdom in this case sasi, regarding the existence of sea cucumbers in Lelingluan village, North Tanimbar District, and Tanimbar Archipelago Regency.